Peran Literasi Digital dalam Meningkatkan Literasi Kesehatan Digital pada Siswa SMK Jurusan Farmasi - I Made Yoga Pramana; Gusti Ayu (Edu Berkah Khatulistiwa, 2026)
The rapid advancement of digital technology necessitates the enhancement of digital literacy as a fundamental competency for accessing, comprehending, and critically evaluating information, including in the health domain. Digital literacy constitutes a crucial foundation for the development of digital health literacy, particularly among vocational high school students majoring in Pharmacy, who are prospective healthcare professionals. This study aims to assess the levels of digital literacy and digital health literacy, and to examine the influence of digital literacy on digital health literacy among Pharmacy students at SMK Bintang Persada Denpasar. This study employed a quantitative analytic descriptive design, involving a sample of 109 students selected through a convenience sampling technique. Data were collected using a validated and reliable questionnaire and subsequently analyzed using descriptive, bivariate, and multivariate approaches, including multiple linear regression analysis. The findings indicate that digital literacy levels were categorized as high in the Digital Skill (53.2%) and Digital Competence (62.4%) dimensions. Meanwhile, digital health literacy was distributed equally between moderate and high categories (48.6%). The results of the regression analysis revealed that Digital Skill (β = 0.342; p = 0.001) and Digital Competence (β = 0.249; p = 0.016) had a positive and statistically significant effect on digital health literacy, accounting for 27.9% of the variance (R² = 0.279). Digital literacy plays a significant role in enhancing digital health literacy.